STUDY OF SEA WATER CIRCULATION AND PARTICLE RESIDENCE TIME IN BENOA BAY, BALI IN THE WET AND DRY SEASONS - Retno Pramesti, Anindya
Benoa Bay is an area that is heavily influenced by daily human activities due to its function as a transportation route and tourism center. Its proximity to industrial areas means that Benoa Bay is often used as a landfill site. This can cause Benoa Bay to experience some environmental issues. Therefore, research related to particle residence time needs to be carried out to determine the particles residence time particle (for example marine debris) in the bay. The calculation of particle residence time was carried out with a combination of hydrodynamic models and particle tracking models using the Finite Volume Coastal Ocean Model (FVCOM) numerical model. Simulations were conducted in the wet and dry seasons to see the influence of river discharge on current circulation patterns and particle residence time. Current conditions in Benoa Bay tend to be influenced by tides with alternating current patterns from southeast to northwest. The maximum current velocity in Benoa Bay reaches a value of 1.065 m/s during spring tides and tends to weaken during neap tides. Particle residence time in the wetseason is dominantly 1?10 day s, while in the dry season it ranges from 11?20 days. Particles tend to be trapped in narrow and closed areas such as the Benoa Harbor dock area with residence time of >40 days.